Respiratory symptoms and use of dust-control measures in New Zealand construction workers - A cross-sectional study - Keer S; Brooks C; Glass B; McLean D; Harding E; Douwes J (PLOS)
Dust-exposed construction workers have an increased risk of respiratory symptoms, but the efficacy of dust-control measures remains unclear. This study compared respiratory symptoms, using a modified European Community Respiratory Health Survey questionnaire, between construction workers (n = 208) and a reference group of bus drivers and retail workers (n = 142). Within the construction workers, we assessed the effect of collective (on-tool vacuum/'wet-cut' systems) and personal (respirators) exposure controls on symptom prevalence. Logistic regression assessed differences between groups, adjusted for age, ethnicity, and smoking status. Construction workers were more likely to cough with phlegm at least once a week (OR 2.4, 95% CI 1.2-4.7) and cough with phlegm ≥3 months/year for ≥2 years (OR 2.8, CI 1.2-7.0), but they had similar or fewer asthma symptoms. Construction workers who had worked for 11-20 years reported more cough/phlegm symptoms (OR 5.1, 1.7-15.0 for cough with phlegm ≥3 months/year for ≥2 years) than those who had worked <10 years (OR 1.9, 0.6-5.8), when compared to the reference group. Those who used 'wet-cut' methods reported less cough with phlegm, although the evidence for this association was weak (OR 0.4, CI 0.2-1.1 for cough with phlegm at least once a week); use of on-tool extraction showed a similar trend. No associations between respiratory protective equipment-use and symptoms were found. In conclusion, construction workers reported more symptoms suggestive of bronchitis, particularly those employed in the industry for >10 years. Use of collective dust exposure controls might protect against these symptoms, but this requires confirmation in a larger study.
© 2022 Keer et al.
Keywords: Construction Industry; Cough; Cross-Sectional Studies; Dust; Humans; New Zealand; Occupational Diseases; Occupational Exposure